Analisis Skore Kondisi Tubuh (SKT) terhadap Keberhasilan Inseminasi Buatan (IB) pada Sapi di Kabupaten Tebo - Fachroerozi Hoesni; Firmansyah Firmansyah; Farizal Farizal; Jalius Jalius (Universitas Batanghari Jambi, 2022)
This study aims to determine the difference in the success rate of Artificial Insemination (AI) and Body Condition Score Analysis (SKT), and to determine the effect of HCS, body weight, and age of cattle on the success of Artificial Insemination (IB) in cattle in Tebo Regency. This research was conducted in Tebo Regency, namely in 3 sub-districts, Rimbo Ilir District, Rimbo Bujang District, and Rimbo Ulu District. The method used is a survey method. The sampling technique uses clustering. The data obtained were then processed using multiple linear regression and analyzed using t-test. The results show that the success rate of Artificial Insemination (IB) in the form of S/C in Tebo Regency is 1.56. The highest value of HCS in Tebo Regency is SKT with a moderate value of (3) as much as 41.18%. The body weight of livestock in Tebo Regency is 350.25 Kg, and the age ranges from 4-8 years. The results of this study revealed that the success of Artificial Insemination (IB) in Tebo Regency was good, there were differences in the value of SKT between sub-districts, and the value of SKT and body weight of livestock did not affect the success of Artificial Insemination (AI) in the form of S/C, while the age of livestock had an influence on the success of Artificial Insemination (IB) in the form of S/C.